Malthusianism of the 21st century - Borja Montano; Marcos García-López (Environmental and Sustainability Indicators, 2020)
This paper has arisen from a reflection of the current reality in terms of the postulations about what is known as the Malthusian economy. Since the Industrial Revolution to the present day, despite there having been a high increase in world population, technology has played a fundamental role in the increase in the level of wealth per capita. However, the continued growth of the population and the future forecasts indicate that technology with have the responsibility of continually being the key piece of economic growth. This paper seeks to analyse the future scenarios in order to better understand the conditioning factors of the sustainability of our population growth. If technology were not able to maintain production growth rates higher than the population growth rates, we would return to the scenario described by Malthus.